HKU Civil Engineering and Computer Science Rank High in 2014 QS University Subject Rankings in Engineering Technology (Hong Kong Government News, 2014)
Hong Kong, Feb. 26 -- HKU Civil Engineering and Computer Science continued to position amongst world-class universities, as evidenced by their latest rankings being at the 10th and 14th respectively in 2014 QS University Subject Rankings in Engineering & Technology, announced on February 26, 2014.